Anxiety and depression scores in patients subjected to aortic and iliac aneurysm repair procedures - Mendes,Cynthia de Almeida (2021)
SUMMARY OBJECTIVE: This study examines the changes in anxiety and depression scores of 84 patients subjected to aortic or iliac aneurysm correction with no previous psychiatric history. METHODS: Patients were referred to the evaluation using the Beck Anxiety and Depression Inventories no more than 3 days before surgery (i.e., preoperative [Pre-Op]), 30 days after revascularization (i.e., Early postoperative [PO]), and at least 6 months after revascularization (i.e., Late PO). RESULTS: Mean anxiety scores declined from baseline at both the Early (mean difference: 2.75, p<0.001) and Late PO (mean difference: 2.74, p=0.001). The depression levels showed no significant variation in either evaluation (Early PO; mean difference: −0.84, p>0.05, Late PO: 0.87, p=0.05). A more severe degree of anxiety at baseline was related to better anxiety results both in the Early PO (p=0.041) and Late PO (p=0.008). An endovascular technique was related to the improvement in depression symptoms in the Early PO (p=0.01) but the worsening of the symptoms in the Late PO (p=0.033). CONCLUSIONS: Patients subjected to aortoiliac aneurysm corrections have a higher incidence of anxiety and depressive symptoms. Anxiety symptoms, but not the depressive ones, improved considerably following the successful treatment. The formal psychiatric evaluation may be beneficial for patients with less improvement in the symptom.